The Price of Living a Philosophical Life Without Object Naturalism - Lawler, Diego; Orlando, Eleonora (Análisis. Revista de investigación filosófica, 2014)
Resumen En nuestro artículo nos centramos en las principales críticas al representacionalismo desarrolladas por Huw Price en su trabajo “Naturalism without Representationalism”, unas críticas que sientan las bases de su primer argumento contra el naturalismo del objeto. Con posterioridad examinamos su segundo argumento, el que se sigue de sus consideraciones sobre la posibilidad de comenzar con una concepción material de los problemas de la localización.   Palabras clave: Huw Price, naturalismo del objeto, naturalismo del sujeto, representacionalismo.   Abstract In our paper we first focus on Price´s central objections to representationalism in his “Naturalism without Rpresentationalism”, which pave the way for his first argument against object naturalism –in his terms, they throw doubts on the possibility of ‘validating’ object naturalism. Then, we will examine his second argument, stemming from his considerations on the possibility of starting off with a material conception of the placement problems   Key Words: Huw Price, object naturalism, subject naturalism, representationalism